Estudo cinético da hidrólise de xilooligômeros por xilanases e beta-xilosidase na forma livre e imobilizada - Baldez, Thaís Oliveira (Universidade Federal de São Carlos, 2018)
This work aims to contribute to the development of the ethanol production process from xylooligomers (XO) extracted from sugarcane bagasse hemicellulose through the hydrolysis of XO to xylose, xylose isomerization catalyzed by xyloseisomerase (XI) and fermentation of the isomer to ethanol by Sacharomyces cerevisiae (Sc). All reactions will occur within a biocatalyst where the enzymes, previously immobilized covalently in other carriers, will be co-immobilized with the yeast in calcium alginate. The efficiency of this process for the production of ethanol has already been demonstrated by DEQ/UFSCar researchers, with an patent application request. The focus of this work is on the hydrolysis stage of XO to xylose, by the actions of endo / exoxylanases, β-xylosidase and auxiliary enzymes (Xyl). The objective of this work was to study different enzymatic cocktails in order to select and characterize the most suitable for the complete hydrolysis of xylooligomers/xylan in xylose. To facilitate this search, it was also necessary to develop a substrate that would allow efficient study of the action of endoxylanases. A xylan with the same commercial performance was then produced and extracted from the bleached eucalyptus pulp (holocellulose). The kinetic study was caried with the enzymes: Multifect A03139 (XAS-2) and Accellerase A03304 (XAS-3), two commercial complexes containing xylanases, auxiliary enzymes and β-xylosidase; a recombinant endo-xylanase from Bacillus subtilis (Verdartis) (XAS-1) and a recombinant in-house produced β-xylosidase (XAS-4). The latter two were also studied in the immobilized form XASI-1 and XASPI-4. The influence of enzyme concentration, temperature, pH and substrate concentration on xylan hydrolysis were evaluated. In addition, the thermal stability of each enzyme was assessed at temperatures of 32 (SHIF process) and 50 ° C. Kinetic models were fitted with initial velocity profiles data to estimate the kinetic parameters of the reactions. The inhibition effect caused by xylose and xylose / xylulose concentrations combined in β-xylosidases was also evaluated. For β-xylosidase (XASPI-4), it was possible to adjust a competitive inhibition model with two inhibitors. The long-term enzymatic hydrolysis assays were carried out with all the enzymes isolated and some combined, to evaluate the production profile of xylooligosaccharides, both at 50 ºC and 32 ºC. The hydrolysis with XAS-1 and XASP-4 combined obtained promising results, since it is possible to observe an increase of the conversion profile and the xylose production after 48 h of reaction. Tests were also carried out at 32ºC with liquors obtained from hydrothermal and alkaline pre-treatments of sugarcane bagasse. The obtained results allow a greater comprehension of each enzymes characteristics, assisting the preparation of an efficient enzymes cocktail to completely convert xylan to xylose.
Kinetic study the hydrolysis of xyloligomers by xylanases and beta-xylosidase in the free and immobilized form
Keywords: Xilana; Xilanases; β-xilosidases; Estudo cinético; Hidrólise enzimática; Xylan; Xylanases; β-xylosidases; Kinetic study; Enzymatic hydrolysis; ENGENHARIAS::ENGENHARIA QUIMICA